Metabolic Mechanisms Connecting Alzheimer’s and Parkinson’s Diseases: Potential Avenues for Novel Therapeutic Approaches - Colca, Jerry R.; Finck, Brian N. (Frontiers in Molecular Biosciences, 2022)
Alzheimer’s (AD) and Parkinson’s Diseases (PD) are common neurodegenerative disorders growing in incidence and prevalence and for which there are no disease-modifying treatments. While there are considerable complexities in the presentations of these diseases, the histological pictures of these pathologies, as well as several rare genetic predispositions for each, point to the involvement of maladaptive protein processing and inflammation. Importantly, the common presentations of AD and PD are connected to aging and to dysmetabolism, including common co-diagnosis of metabolic syndrome or diabetes. Examination of anti-diabetic therapies in preclinical models and in some observational clinical studies have suggested effectiveness of the first generation insulin sensitizer pioglitazone in both AD and PD. Recently, the mitochondrial pyruvate carrier (MPC) was shown to be a previously unrecognized target of pioglitazone. New insulin sensitizers are in development that can be dosed to full engagement of this previously unappreciated mitochondrial target. Here we review molecular mechanisms that connect modification of pyruvate metabolism with known liabilities of AD and PD. The mechanisms involve modification of autophagy, inflammation, and cell differentiation in various cell types including neurons, glia, macrophages, and endothelium. These observations have implications for the understanding of the general pathology of neurodegeneration and suggest general therapeutic approaches to disease modification.